THE CRITICAL SUCCESS FACTORS MODEL FOR IMPLEMENTATION OF ENTERPRISE ARCHITECTURE IN PDAM TIRTA RAHARJA - Editha Dewi Purnama Sari (IST AKPRIND Yogyakarta, 2018)
Implementation of Enterprise Architecture (EA) is define as a way that can help align and retain business-Information Technology (IT) to acquire economic, technological, and strategic advantage. In regard on current technology advances, businesses in organizations are required to be more rapidly adapted. Therefore, implementation of EA becomes the right choice. However, it is not easy to achieve goals in EA implementation because it is inflexible and complexity of the business an IT structure in the organization, so that the implementation of EA in the organization fails. There is a critical success factor (CSF) taken as a reference that the successful implementation of EA. Specifiacally, these factors are Communication and Support, EA Model, Business Driven Approach, Organizational Culture, Training/Education, Governance, and Stakeholder Participant. Each of these factors has the potential to support the successful implementation of EA. This study aims to examine the relationship and influence of critical success factors on the Successful Implementation of EA. This research uses quantitative research method involving PDAM Tirta Raharja, IS Student, and general public with survey data of 12 articles (journals and conference papers), online questionnaire filled by 40 respondents and data analysis using SPSS 23 software with Multiple Regression Test. The result of this research is CFS Model for EA implementation, there are 4 CSF which have significant influence that is Communication and Support, Business Based Approach, Stakeholder and Organizational Culture. Finally, it provides critical success factors (CSFs) to achieve successful EA implementation and to benefit companies.